Hari Hara Temple no. 2 at Osian in Rajasthan - Temples of India Project Team (Jio Institute, 2024)
Hari Hara Temple no. 2. Osian, Rajasthan, India. Gurjara Pratihara period, ca. mid-8th century CE. Image courtesy: Prof. Chedha Tingsanchali.